Off-Season cultivation of several shallot varieties in dry land, Lampung. Issue 4 (July 2021) - Wardani, N; Mulyanti, N; Mustikawati, D R; Lasmono, A; Sinaga, R; Ulfa, F
Abstract: Lampung is one of the centers for shallot development in Indonesia. The application of location-specific off-season shallot cultivation technology and the use of superior varieties is expected to be able to guarantee its availability throughout the year and overcome price fluctuations. For this reason, it is necessary to study the cultivation of off-season shallots with varieties in accordance with market demand. This activity was carried out in Tanggamus Regency, from January to December 2018. The experimental design was the Split Plot, where the main plot was the use of mulch and without mulch and as sub-plots were three shallot varieties, namely: 1. Bima Brebes; 2. Trisula; and 3. Bali Karet varieties. Each treatment was repeated four times. The data obtained were analyzed using variance with DMRT at the 5% level. The results of the study show that off-season shallot cultivation is promising to be cultivated by farmers with an average of 14.59 tonnes/ha using Bima Brebes, Trisula, and Bali Karet varieties. Bali Karet variety has good prospects to be developed and planted off-season because they are more resistant to pests and diseases and have the highest production (20.87 tonnes/ha) compared to Bima Brebes and Trisula varieties.